An autonomous lunar geophysical experiment package (ALGEP) for future space missions: In response to Call for White Papers for the Voyage 2050 long-term plan in the ESA Science Program - Kawamura, T.; Grott, M.; Garcia, R.; Wieczorek, M.; de Raucourt, S.; Lognonné, P.; Bernauer, F.; Breuer, D.; Clinton, J.; Delage, P.; Drilleau, M.; Ferraioli, L.; et al. (SPRINGER, 2022)
Geophysical observations will provide key information about the inner structure of the planets and satellites and understanding the internal structure is a strong constraint on the bulk composition and thermal evolution of these bodies. Thus, geophysical observations are a key to uncovering the origin and evolution of the Moon. In this article, we propose the development of an autonomous lunar geophysical experiment package, composed of a suite of instruments and a central station with standardized interface, which can be installed on various future lunar missions. By fixing the interface between instruments and the central station, it would be possible to easily configure an appropriate experiment package for different missions. We describe here a series of geophysical instruments that may be included as part of the geophysical package: a seismometer, a magnetometer, a heat flow probe, and a laser reflector. These instruments will provide mechanical, thermal, and geodetic parameters of the Moon that are strongly related to the internal structure. We discuss the functionality required for future geophysical observations of the Moon, including the development of the central station that will be used commonly by different payloads.